1998
DOI: 10.1093/dote/11.1.35
|View full text |Cite
|
Sign up to set email alerts
|

CYFRA 21–1 as a tumor marker for squamous cell carcinoma of the esophagus

Abstract: This study assessed the clinical value of CYFRA 21-1 in comparison with squamous cell carcinoma antigen (SCC-Ag), carcinoembryonic antigen (CEA), and carbohydrate antigen 19-9 (CA19-9) in patients with esophageal squamous cell carcinoma. In 112 primary cancer patients, the diagnostic sensitivity of CYFRA 21-1 (33.9%) was superior to SCC-Ag (28.6%), CEA (12.5%), and CA19-9 (6.3%). Levels of CYFRA 21-1 were closely correlated with TNM stage and were below the cutoff value in all 21 patients with stage I disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 0 publications
4
39
2
Order By: Relevance
“…Data from other researchers is similar ranging be- 17 noted that the diagnostic sensitivity of CYFRA 21-1 (33.9%) was superior to SCC antigen (28.6%) and CEA (12.5%). In the current study, the sensitivity of CYFRA 21-1 (43.9%) was found to be superior than that of SCC antigen (26.8%) and CEA (17.0%).…”
Section: Discussionsupporting
confidence: 77%
“…Data from other researchers is similar ranging be- 17 noted that the diagnostic sensitivity of CYFRA 21-1 (33.9%) was superior to SCC antigen (28.6%) and CEA (12.5%). In the current study, the sensitivity of CYFRA 21-1 (43.9%) was found to be superior than that of SCC antigen (26.8%) and CEA (17.0%).…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, the acidic form is the dominant form of the serum SCC and it is thought to be secreted by malignant cells. However, the sensitivity of the serum SCC antigen is 28.6-37% (Mealy et al, 1996;Nakamura et al, 1998;Quillien et al, 1998) in oesophageal cancer. Therefore the acidic form may not always be produced in oesophageal cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…The specificity, sensitivity and accuracy of CYFRA21-1 were 100%, 47.9% and 66.7%, respectively. Nakamura et al (1998) reported that there is a correlation between CYFRA21-1 levels and clinical responses in patients who received chemotherapy or CRT. CYFRA 21-1 correlates better with the pathologic TNM stage.…”
Section: Discussionmentioning
confidence: 99%